Bimbingan Teknis Olahan Pangan Hewani untuk Meningkatkan Pengetahuan TP PKK Desa Jatinom, Kabupaten Blitar - . Lestariningsih; Peni Nohantiya (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
The purpose of this dedication to miter increase knowledge on animal food potential benefited in the miter village. That was cause the problem of miner less understand technology to process animal food. Besides, Jatinom village had animal food pontential. Jatinom society used animal food such as milk and egg only to side dish in their family. Besides, many inhabitant works in the farm of animal as farmer and employees. Therefore, they have opportunity to get animal material product with low prices. When it proceses better so its can get high prices. By of this dedication, official give solution on the miter problem to pioneer movement proceses of animal food had economic value with proceses animal food guidance. Specially target in this dedication, its to increase miter knowledge on animal food proceses to get high prices. The methods used observation, interview, and partnership to finish the problems there with 12 times in the week as long this dedication in December 2017, prepare the planning program such as give guidance about important of animal food process to increase miner knowlegde (TP PKK Jatinom Village). The result of this dedication was guidance animal food process can open knowledge to increase miner productive (TP PKK Jatinom Village, Kanigoro Subdistrict, Blitar District). The dedication need to follow by direct coaching animal food proceses.